101k views
4 votes
Df = 9x -39 find EF.
DE =47

Df = 9x -39 find EF. DE =47-example-1
User Ron Jonk
by
4.8k points

1 Answer

5 votes

Greetings from Brasil....

Looking at the figure we can say that:

DF = DE + EF

DF = 9X - 39

DE = 47

EF = 3X + 10

inserting these data in the 1st expression....

DF = DE + EF

9X - 39 = 47 + (3X + 10)

9X - 39 = 47 + 3X + 10

9X - 3X = 57 + 39

6X = 96

X = 96/6

X = 16

EF = 3X + 10 anb X = 16, so

EF = 3ยท16 + 10

EF = 48 + 10

EF = 58

User Sascha Kolberg
by
5.1k points